Development of Healthy School Module for Early Hypertension Prevention Among Urban Adolescents - Aneng Yuningsih; Idhfi Marpatmawati; Betty Suprapti; Salma Maulida; Mia Ruhmiati; Nuraeni Nuraeni; Shaila Rizki (LP3M Universitas Muhammadiyah Tasikmalaya, 2026)
Sedentary behavior, high sodium intake, and poor sleep hygiene trigger early hypertension risks among urban adolescents, creating a distinct knowledge-practice gap (KAP gap). This study aimed to develop, validate, and evaluate the effectiveness of the Healthy School Intervention Module for the early prevention of hypertension among urban adolescents. This Research and Development (R&D) study conducted a limited field trial involving 15 students at SMAN 8 Tasikmalaya selected via criterion sampling. Data were collected using expert validation sheets, KAP questionnaires (pre-post test), and clinical blood pressure screenings. Two experts validated the module as highly feasible (90%). Post-intervention, significant improvements were observed in knowledge (+10.37%; 4.53 ± 0.52 to 5.00 ± 0.00), attitude (+11.11%; 14.40 ± 1.55 to 16.00 ± 0.00), and practice (+35.50%; 6.00 ± 1.13 to 8.13 ± 0.64), successfully exceeding the >20% success indicator. Bivariate analysis demonstrated a statistically significant reduction in systolic and diastolic blood pressure among overweight/obese students (P < 0.05). The Healthy School Intervention Module is highly feasible and effective in enhancing KAP performance and optimizing clinical blood pressure profiles toward a healthier lifestyle.